2006
DOI: 10.1111/j.1468-2982.2006.01114.x
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Type A in the Prophylactic Treatment of Chronic Tension-Type Headache: A Multicentre, Double-Blind, Randomized, Placebo-Controlled, Parallel-Group Study

Abstract: We studied the safety and efficacy of 0 U, 50 U, 100 U, 150 U (five sites), 86 Usub and 100 Usub (three sites) botulinum toxin type A (BoNTA; BOTOX®; Allergan, Inc., Irvine, CA, USA) for the prophylaxis of chronic tension-type headache (CTTH). Three hundred patients (62.3± female; mean age 42.6 years) enrolled. For the primary endpoint, the mean change from baseline in the number of TTH-free days per month, there was no statistically significant difference between placebo and four BoNTA groups, but a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
91
0
6

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(103 citation statements)
references
References 37 publications
6
91
0
6
Order By: Relevance
“…As migraine has peripheral and central mechanisms, it is possible that BT-A can influence pain perception in different levels of the peripheral and central nervous system in a way not yet established. Results of all studies published up to now have shown BT-A to be safe and well tolerated, and it its action was observed up to four months 12,13 , making it an alternative to patients in whom other therapeutic options to migraine have failed. Both of them had better response than the placebo group 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As migraine has peripheral and central mechanisms, it is possible that BT-A can influence pain perception in different levels of the peripheral and central nervous system in a way not yet established. Results of all studies published up to now have shown BT-A to be safe and well tolerated, and it its action was observed up to four months 12,13 , making it an alternative to patients in whom other therapeutic options to migraine have failed. Both of them had better response than the placebo group 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Although many open trials have demonstrated improvement in patients with chronic tension type headache 10,11 , the controlled double blind trials did not support these results [12][13][14] .…”
mentioning
confidence: 99%
“…For tension headache-free days per month, all groups improved at the day 60 primary endpoint, while after 90 days a 50% decrease in terms of headache days was observed in BoNT-A patients. This suggests the necessity of a longer evaluation period [27].…”
Section: Bont-a In Headache Treatmentmentioning
confidence: 99%
“…Thus, a clinically meaningful effect of BoNT was excluded. The other Class I study 34 used as primary outcome the mean change from baseline in number of headache-free days from day 30 to 60 after injection. Both BoNT and placebo groups improved after injection, but BoNT was not more beneficial.…”
Section: Recommendationsmentioning
confidence: 99%